Penerapan Air Deffense Identification Zone (ADIZ) Sebagai Upaya Pertahanan Ruang Udara Indonesia - Tri Bowo Hersandy Febrianto; Irwan Triadi (Lembaga Pengembangan Kinerja Dosen, 2023)
The establishment of an ADIZ in each country is one step in maintaining the sovereignty of each country. This has been a long debate because there are no regulations outlined in international legal conventions. Until now, ADIZ Indonesia is only limited to the island of Java, so the role of ADIZ has not been effective in protecting air space which is included in the country's sovereignty. This research aims to explain the role of ADIZ as a first step in efforts to maintain state sovereignty from the perspective of international and national law. The normative juridical approach method is an approach based on the main legal material by examining theories, concepts, legal principles and statutory regulations. The research results show that Indonesia needs to re-establish ADIZ not only around the island of Java but also covering the entire sovereign territory of the country.